The Influence of Maternal Characteristics on The Quality of Life of Postpartum Mothers - Aziza, Adelia Nur; Rahayuningsih, Faizah Betty (Universitas Muhammadiyah Surakarta, 2022)
Purpose: To determine the influence of postpartum maternal characteristics on the quality of lifeMethodology: This study is a correlational, quantitative study using a cross-sectional approach. This research instrument uses a questionnaire with a questionnaire compiled by Hill called Maternal Postpartum Quality of Life. 61 respondents were involved in the study. Results: The study's results with the Pearson Product Moment correlation test showed a weak relationship between the mother's age, the week of pregnancy, the number of maternal pregnancies, the number of maternal births, the number of live children, and birth weight. Based on the ANOVA test, the results showed an influence between living together, working, and profession with the mother's quality of life.Applications/Originality/Value: The difference between this research and previous research lies in the research respondents, research time, measuring instruments, literature used, theories used, and results from research. Further research can be carried out on more diverse targets.